Co-firing of paper sludge with high-calorific industrial wastes in a pilot-scale nozzle-grate incinerator - Lee, GW; Lee, SJ; Jurng, J; Hwang, J (ELSEVIER SCIENCE BV, 2003)
Experiments on the co-firing of high-calorific industrial wastes with paper sludge were performed in a pilot-scale industrial waste incinerator with a nozzle-type grate system. The incineration capacity was approximately 160 kg/h. The temporal variations in the temperatures and exhaust gas emissions were monitored and used as parameters for determining the desirable incineration conditions. The high CO emissions that were mainly due to the rapid vaporization of combustibles from high-calorific industrial wastes could be alleviated through the co-firing of sludge with the high-calorific industrial wastes. Because of the high nitrogen content in the sludge, the increase in the co-firing rate caused higher NO emissions in the flue gas. If the total calorific value of the feed was lower than 750,000 kca/h, for 25-30% of sludge co-firing, the temperature of gases exiting the secondary combustion chamber might be lower than that required by regulations. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: FLUIDIZED-BED